La gestión del docente como vínculo en la convivencia de género en la Unidad Educativa Isidro Ayora de la ciudad de Latacunga - Guamani Jaya, Blanca Marisol (2016)
Teacher management as gender living together link on the Educative Unite Isidro Ayora of Latacunga Present research was based on teacher management and gender cohabitation into teaching learning process, in function to get better the educative community cooperation, through ludic activities projection which ones help to make better the scholastic relation. The general education has as argue the inclusion marked on The Buen Vivir like transversal axis for team working innovation. The investigation was based on qualitative and quantitative study, by data recollection and information processing to understand, analyzing, and interpreting it with educative phenomena and explains it truly. The Propose of this investigative job was established onto activities to increase contribution habits those will be used to develop the institution´s image and to create spaces for gender equality on correct way among educative actors.